Caudal regression syndrome (sirenomelia) and its pathogenesis correlation: a case report - Rani, Vanadondi Usha; Rao, Nakka Sreekantha; Kumar, Chaluvadi Jwalaram; Saritha, Seethamsetty (International Journal of Research in Medical Sciences, 2017)
Congenital anomaly characterized by an abnormal development of caudal region of the body with different degrees of fusion of lower extremities, bears resemblance of Sirenomelia or mermaid of Greek Mythology. This type of deformity is also known as Symmelia, Symposia, Sympus, Uromelia and Monopodia. It is associated with the single umbilical artery. It is associated with severe malformations of urogenital i.e. renal agenesis and absence of both internal and external genitalia. The aim of this study is to present, a rare congenital malformation Sirenomelia. In this context, we report a case of Sirenomelia illustrating the prenatal sonographic and pathological features. In our study 25 years old primigravida gave birth to still born full term baby, sex could not be identified. The specimen was collected from private nursing home at Ongole, no relevant history of consanguineous marriage or tobacco smoking or drugs taking etc. Fetal USG, X-ray & CT were taken after birth. Fetal autopsy was done; the gonad, thymus and umbilical cord were sent to histopathological examination. The etiopathogenesis and characteristic features of Sirenomelia were discussed with the findings and review of the literature.